Análise comparativa da eficiência fotodinâmica de fotossensibilizadores em sua forma base livre e formando complexados com zinco - Alonso, Lais (2014)
Photodynamic therapy (PDT) is a technique that has been increasingly used in cancer treatment. It consists in introduce a photosensitizer (PS) in cancerous tissue and irradiate it with light in the visible range. Targeting a more effective treatment of PDT, currently there are several studies on the efficacy of these PS. In this work, we studied the photodynamic efficiency seven PS: meso-tetrametilpiridil, meso-tetrasulfonatofenil and carboxiftalocianinas with their base free or metallated with zinc atom in its center ring and protoporphyrin IX. Erythrocytes suspended in 2 to 10% hematocrit were treated with or without 25 μM of PS were exposed to light from a halogen lamp, and measured the time required to obtain 50 % hemolysis (T1/2). To examine whether the photodynamic efficiency is related to the affinity of PS by membrane, we performed measurements of the octanol/water partition coefficient (PO/W) of each PS. Our results indicated that the PS studied were very hydrophilic and showed a trend for greater photodynamic efficiency the PS with higher Log PO/W. To better understand the mechanism of action of the studied PS the degree of lipid peroxidation in erythrocyte membranes irradiated with PS was assessed by measuring the formation of malondialdehyde (MDA) and a correlation between the rate of peroxidation and hemolytic potential was found. The ability of PS to degrade proteins was assessed using bovine serum albumin (BSA), monitoring the fluorescent signal of this protein into solution and under irradiation in the presence of PS.